Implementasi Konsep Net Zero Healthy Pada Bangunan Sekolah - Antoni, Febri; Kusumawati, Lili; Kurniyaningrum, Endah; Pontan, Darmawan; Widiarso, Tulus (Riviera Publishing, 2025)
This study aims to evaluate the implementation of the Net Zero Healthy (NZH) concept in a total school rehabilitation project in DKI Jakarta Province, as an effort to develop energy-efficient buildings that also promote physical health and thermal comfort for occupants. Employing a qualitative case study approach, data were collected through in-depth interviews, field observations, document analysis, and questionnaires from building users. The results indicate that solar panels effectively supplied 15% of the school’s total energy needs, although constrained by regulations. Furthermore, all working spaces met the minimum standards for natural ventilation and daylighting based on ASHRAE and Indonesian national standards. Mechanical ventilation through fans also performed optimally, supplying fresh air significantly above the required minimum. These findings demonstrate that NZH principles can be effectively applied to public building projects by considering design, technology, and user behavior. This research contributes significantly to green building policy development and national emission reduction efforts.